Bitter melon fruit extract enhances intracellular ATP production and insulin secretion from rat pancreatic β-cells. Issue 3 (14th February 2022) - Shimada, Takumi; Kato, Fumihiro; Dwijayanti, Dinia Rizqi; Nagata, Takuma; Kinoshita, Akito; Okuyama, Tetsuya; Nishizawa, Mikio; Mukai, Eri
Abstract: Bitter melon ( Momordica charantia L.) has been shown to have various health-promoting activities, including antidiabetic and hypoglycaemic effects. Improvement in insulin sensitivity and increase in glucose utilisation in peripheral tissues have been reported, but the effect on insulin secretion from pancreatic β -cells remains unclear. In this study, we investigated the effect of bitter melon fruit on insulin secretion from β -cells and the underlying mechanism. The green fruit of bitter melon was freeze-dried and extracted with methanol. The bitter melon fruit extract (BMFE) was fractionated using ethyl acetate (fraction A), n -butanol (fraction B) and water (fraction C). Insulin secretory capacity from INS-1 rat insulinoma cell line and rat pancreatic islets, as well as glucose tolerance in rats by oral glucose tolerance test (OGTT), was measured using BMFE and fractions. ATP production in β -cells was also examined. BMFE augmented insulin secretion from INS-1 cells in a dose-dependent manner. The significant augmentation of insulin secretion was independent of the glucose dose. Fraction A (i.e. hydrophobic fraction), but not fractions B and C, augmented insulin secretion significantly at the same level as that by BMFE. This finding was also observed in pancreatic islets. In OGTT, BMFE and fraction A decreased blood glucose levels and increased serum insulin levels after glucose loading. The decrease in blood glucose levels was also observed in streptozotocin-induced diabetic rats. In addition, BMFE and fraction A increased the ATP content in β -cells. We concluded that hydrophobic components of BMFE increase ATP production and augment insulin secretion from β -cells, consequently decreasing blood glucose levels.